2013
DOI: 10.1111/ans.12076
|View full text |Cite
|
Sign up to set email alerts
|

Alvarado score: a guide to computed tomography utilization in appendicitis

Abstract: In suspected appendicitis, patients who benefit from CT evaluation are those with the AS ranging from 4 to 8. We propose a management algorithm with the AS guiding the necessity for CT evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Emergency service physicians encounter patients with abdominal pain many times a day and try to differentiate between these diagnoses. Tan and et al [5] have stated that abdominal CT is especially important for suspected cases for diagnosis in their study. They have found that patients undergoing CT evaluation have a negative appendectomy rate of 5.7% compared to 17.9% in those without CT evaluation in suspected cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Emergency service physicians encounter patients with abdominal pain many times a day and try to differentiate between these diagnoses. Tan and et al [5] have stated that abdominal CT is especially important for suspected cases for diagnosis in their study. They have found that patients undergoing CT evaluation have a negative appendectomy rate of 5.7% compared to 17.9% in those without CT evaluation in suspected cases.…”
Section: Discussionmentioning
confidence: 93%
“…In cases where differential diagnosis is challenging, an experienced ultrasonographer cannot be always accessible. [5] Non-contrasted and/or contrast-enhanced abdominopelvic tomography (CT) requires a specialist for its interpretation, not mentioning exposure to the risks of radiation and contrast agent hypersensitivity. This condition can leave the patient and the physicians in a difficult dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…numerous scoring systems evaluating clinical symptoms and blood tests to increase the prognostic accuracy of appendicitis have been designed (7)(8)(9). However, none of the scoring systems evaluate the risk of appendiceal perforation, and none of the scoring systems use a combination of blood markers.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 We previously proposed a management algorithm guiding CT use for suspected appendicitis based on the AS. 10 This was, however, derived from retrospective data with its antecedent limitations. So, we aimed to compare the performance statistics of the AS with CT scan in the evaluation of suspected appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…9 We previously proposed a management algorithm for suspected appendicitis with the Alvarado score (AS) ( Table 1) guiding CT use. 10 This algorithm was, however, developed based on retrospective data with its antecedent limitations.…”
mentioning
confidence: 99%